2017
DOI: 10.1007/s13202-017-0385-4
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of fluids in irregular capillary tubes: a new capillary model based on the single-corner capillary

Abstract: A new basic single-corner capillary model is presented. In this model, the distribution of immiscible fluids is determined by a particular threshold pressure.Additionally, we derive and analyze the interface curvature and profile of the fluid menisci in different tubes. Various polygonal cross sections are obtained by repeatedly superposing the basic single-corner capillary model. We study the relationship between the number of polygon edges and the distribution of fluids as well as the saturation of the wetti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…The oil in the triangular crosssectional capillary is the first to be separated, the square cross section is the second, and the regular pentagonal cross section is the last. According to previous research [33] and the results of the current study (Figure 4), when the number of sides of a cross section increases, and the high-order polygon gradually approaches a circle, the saturation of the water phase decreases. Otherwise, the saturation of the water phase increases, and the water channels become larger.…”
Section: Pressure Drop In Different Capillariessupporting
confidence: 83%
“…The oil in the triangular crosssectional capillary is the first to be separated, the square cross section is the second, and the regular pentagonal cross section is the last. According to previous research [33] and the results of the current study (Figure 4), when the number of sides of a cross section increases, and the high-order polygon gradually approaches a circle, the saturation of the water phase decreases. Otherwise, the saturation of the water phase increases, and the water channels become larger.…”
Section: Pressure Drop In Different Capillariessupporting
confidence: 83%
“…They also concluded that there exists a capillary flow limit. Other notable works on capillary-driven flow in open grooves can be found in [7][8][9][10][11][12][13] . More recently, attention has been given to surface properties and its effect on capillary rise.…”
Section: List Of Symbolsmentioning
confidence: 99%
“… 31 They introduced a dimensionless shape factor ( G ) based on the perimeter and area of the cross-section and determined the equivalent shape factors for various geometries. 17 , 31 Ponomarenko et al (2011) derived a general law for the capillary rise of wetting liquids in the corner of various geometries. 32 …”
Section: Introductionmentioning
confidence: 99%
“… 36 Long and Zhang (2017) analyzed the distribution of fluids and interface curvature based on single-corner capillary model in irregular capillary tubes. 31 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation